Botulinum toxin use in neurology: Experience at Guillermo Almenara Irigoyen EsSalud Hospital - ROJAS, ÉDGARD (2004)
Objective: To identify the utility, characteristics, outcome and adverse effects in the use of botulinum toxin in neurological disorders. Setting: EsSalud’s Guillermo Almenara National Hospital, Lima, Peru. Materials and Methods: One hundred and twenty-two patients received botulinum toxin type A in different neurological disorders. We determined the characteristics, outcome and adverse effects with the use of botulinum toxin. Results: The most frequent diagnosis was hemifacial spasm (63,1%), followed by spasticity (16,4%) and cervical dystonia (11,5%). The age of hemifacial spasm most frequent presentation was 60 to 69 year-old and in the left side. Torticollis and laterocollis were the most frequent types of cervical dystonia where botulinum toxin was used. There was good response in the treatment according to the favorable outcome by the TWSTRS scale performed before and 3 months posterior to treatment. The main reversible adverse effects were dry eye (15,6%), ecchymosis (9,1%) and pain at the site of application (7,8%). Conclusion: Botulinum toxin type A has many applications in neurological disorders, with good response and few adverse effects.